Early Children's Education Management at GMIM Betlehem Kindergarten Level II - Rumondor, Susana Silvia (International Journal Labs, 2023)
The management of Early Childhood Education (PAUD) at GMIM Betlehem Kindergarten Tataraan II Tondano presents challenges that demand attention. This study delves into the intricacies of PAUD management implementation. Conducted at the Ministry of Education of the Republic of Korea (GMIM), the research scrutinizes the management practices within the institution. The data collection employed a combination of documentation, observation, and interview methods. The evaluation of PAUD management yields insightful findings. Notably, observation proves to be an effective tool in fostering students' object recognition and social abilities. Several components constitute the management of PAUD at GMIM Betlehem Kindergarten Tataraan II. The meticulous planning involves formulating a vision, mission, and institutional objectives, creating a comprehensive academic calendar, developing yearly programs structured into semesters, and crafting weekly and daily activity plans. Despite these efforts, the program's yearly updates lack responsiveness to on-the-ground developments. Implementation faces challenges due to insufficient teaching staff, a consequence of the substantial number of students in each class. Evaluating student progress is crucial, with the research emphasizing two stages: learning assessment and progress reporting. The assessment incorporates techniques such as observation, performance demonstrations, and anecdotal records. The findings contribute to the ongoing discourse, serving as a benchmark for educators to refine future teaching plans. In essence, addressing the complexities of PAUD management at GMIM Betlehem Kindergarten Tataraan II requires strategic planning, sufficient staffing, and a commitment to adapting programs based on regular assessments.